The Effect of Using Powtoon Media on Elementary School Students' Mathematics Learning Outcomes on Time Measurement Material - Wahyu Ari Prasetyo; Sri Hartatik; Nafiah Nafiah; Afib Rulyansah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
Elementary school students tend to experience boredom when studying mathematics, because teachers have not used interesting learning media so that student learning outcomes decrease. This research aims to determine the effect of using Powtoon media on mathematics learning outcomes on the topic of time measurement for fifth grade elementary school students. This type of quantitative research uses the Pre-Experiment Design method with One Group Pre-Test Post-Test Design. The data collection technique was a written test with a saturated sample in class V, totaling 15 students. Data analysis uses Non-Parametric Inferential Statistics with the Wilcoxon Signed Rank Test and Descriptive Statistics. This research uses a data normality test with the Shapiro Wilk Test. Before being given treatment, the average pre-test score for students was 58.66% and after being treated with Powtoon media there was a significant increase with the average post-test score increasing to 76.00%. The results of the Wilcoxon Signed Rank Test show the value of Asymp.Sig. (2-tailed) is 0.002. Because this value is less than <0.05, Ha is accepted. It can be concluded that the use of Powtoon media has an influence on mathematics learning outcomes on the topic of measuring time for class V students. This research includes increasing the use of interactive learning media in the educational process, provides empirical evidence about the effectiveness of Powtoon media in improving student learning outcomes, which can be used as a reference for teachers and curriculum developers to improve the quality of mathematics learning.